Sosialisasi Pendidikan Terkait Pemahaman Demokrasi terhadap Anak Usia Dini di Desa Taman Kecamatan Jrengik Kabupaten Sampang - Raka Satya Dwiantama; Sumriyah Sumriyah (Jurnal Kabar Masyarakat, 2024)
Democracy is a system carried out in government where all people participate in governing and governing their country through the intermediary of the people's representatives. This service is entitled "Socialization of Education Related to Democratic Understanding of Early Childhood in Taman Village, Jrengik District, Sampang Regency" which aims to educate and provide early knowledge to early childhood regarding the importance of democracy, democratic values and democratic principles. The method of implementing this socialization is carried out through interactive activities, the delivery of relevant and understood material, and ends with a discussion. With this activity, children can understand democracy early and can also understand the importance of participating in the democratic process later in the future.